2020
DOI: 10.1016/j.jhsg.2019.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Return to Work Following Complex Nerve Lacerations in the Volar Forearm in an Underserved Spanish-Speaking Population

Abstract: Purpose: Lacerations to the ulnar and median nerve in the volar forearm have demonstrated considerable long-term clinical and socioeconomic impacts on patients. The purpose of this study was to evaluate the outcomes of complex volar forearm lacerations involving one or more major peripheral nerves in an economically disadvantaged patient population. Methods: In this study, a retrospective analysis of 61 patients who sustained lacerations to the median nerve, ulnar nerve, or both with volar wrist lacerations wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…30–34) are in agreement with the results of a previous study of individuals with similar injuries (i.e. 29–31) [ 40 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…30–34) are in agreement with the results of a previous study of individuals with similar injuries (i.e. 29–31) [ 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…injuries. Furthermore, no difference in QuickDASH scores 12 months postoperatively between men and women with median (30 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and 28 ; p = 0.580), ulnar (34 and 34 ; p = 0.716), or radial (17 and 14 ; p = 0.966) nerve injuries were found. Concomitant injuries were equally common among women and men regardless of injured nerve trunk.…”
Section: Plos Onementioning
confidence: 99%
“…This difference persisted even after adjusting for age, sex, immigration, sick leave, education, manual work, cohabitation, income, and diabetes status. These findings align with prior research, where QuickDASH scores for surgically treated digital nerve injuries were generally lower (mean score 7–9) 24 , 25 than those for individuals with a surgically treated major nerve trunk injury (mean score 29–31) 26 . Digital nerve injuries primarily affect finger sensation and fine motor skills, whereas major nerve trunk injuries impact both arm and hand motor function and sensation 27 , 28 , and both types of nerve injuries have a risk of residual pain problems, despite surgery.…”
Section: Discussionsupporting
confidence: 88%
“…Educational disparities can lead to more significant bodily pain, partly attributed to health literacy 35 . Previous research on manual laborers also reported worse motor recovery and lower return-to-work rates compared to office workers, with a median QuickDASH score at 12 months of 34 vs. 27, respectively 26 . Psychosocial factors, including depression, coping strategies, and anxiety, can influence outcome, like pain level, patient satisfaction, and disability 36 .…”
Section: Discussionmentioning
confidence: 85%
“…[ 2 ] Complex hand injuries may cause lifelong impairment associated with social and economic difficulties. [ 3 , 4 ] Many researchers have sought factors influencing the functional recovery of patients with extensive volar forearm lacerations. Advanced patient age, more proximal injuries, injuries to the ulnar nerve (compared to the median nerve), injuries to multiple nerves, and concomitant injuries to tendons and arteries predispose to poor outcomes.…”
Section: Introductionmentioning
confidence: 99%